2013
DOI: 10.1007/s12032-012-0450-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes in elderly patients administered gefitinib as first-line treatment in epidermal growth factor receptor-mutated non-small-cell lung cancer: retrospective analysis in a Nagano Lung Cancer Research Group Study

Abstract: ABSTRACT[214 words (do not exceed 250)]Purpose: The clinical efficacy and outcomes of gefitinib therapy as a first-line treatment for elderly patients with non-small cell lung cancer (NSCLC) with epidermal growth factor receptor (EGFR) mutations were analyzed retrospectively. Patients and methods:We analyzed chemotherapy-naïve NSCLC patients aged 75 years or older who had EGFR mutations (exon 19 deletion mutation or L858R), who were initially treated with gefitinib (250 mg) once daily in Nagano Prefecture.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 23 publications
(28 reference statements)
4
18
0
Order By: Relevance
“…We identified four prospective and two retrospective studies. However, patients of one prospective study [16] were included as patients of another retrospective study [21]; therefore, the prospective study was excluded from our compilation ( [17]. Based on the results of this compilation, we confirmed that the prevalence of female patients, adenocarcinoma, and non-smokers among elderly NSCLC patients was consistent with that reported previously [26].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We identified four prospective and two retrospective studies. However, patients of one prospective study [16] were included as patients of another retrospective study [21]; therefore, the prospective study was excluded from our compilation ( [17]. Based on the results of this compilation, we confirmed that the prevalence of female patients, adenocarcinoma, and non-smokers among elderly NSCLC patients was consistent with that reported previously [26].…”
Section: Discussionsupporting
confidence: 82%
“…Interestingly, several previous clinical trials have examined the efficacy of gefitinib as a first-line treatment for elderly patients with NSCLC harboring sensitive EGFR mutations [15][16][17][18][19][20][21]. Their results suggest that first-line gefitinib is preferable to standard therapy in elderly patients.…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, Tateishi et al confirmed the strong activity and the favourable safety profile of gefitinib in a retrospective analysis among 55 chemotherapy-naïve EGFR mut? NSCLC patients aged 75 years or older [55].…”
Section: Egfr-tkis In Elderly Egfr Mut1 Nsclc Patientsmentioning
confidence: 99%
“…However, these clinical trials were usually conducted only or mainly in healthy patients aged 75 years or younger. In elderly patients with advanced EGFR-mutated NSCLC, some reports [13][14][15] showed the efficacy and safety of gefitinib. However, to our knowledge, the antitumor effects and safety profiles of erlotinib focused on elderly patients have not been evaluated.…”
Section: Introductionmentioning
confidence: 99%